2010
DOI: 10.1175/2010jtecha1481.1
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Controlled Upper-Air Sounding Dataset for TiMREX/SoWMEX: Development and Corrections

Abstract: During the Terrain-Influenced Monsoon Rainfall Experiment (TiMREX), which coincided with Taiwan's Southwesterly Monsoon Experiment-2008 (SoWMEX-08), the upper-air sounding network over the Taiwan region was enhanced by increasing the radiosonde (''sonde'') frequency at its operational sites and by adding several additional sites (three that were land based and two that were ship based) and aircraft dropsondes. During the special observing period of TiMREX (from 15 May to 25 June 2008), 2330 radiosonde observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…The correction was seldom more than 5 % RH when the RS92 temperature exceeded −60 • C. The correction was large for RS92 radiosonde values in the range 15-50 % RH and temperatures of −80 • C, with a maximum of +8.93 % RH. This pattern is similar to that of the correction table for the RS80 radiosonde in the daytime reported by Ciesielski et al (2010) (their Fig. 7b), but the values in Table 5 are much smaller.…”
Section: Humidity Correctionsupporting
confidence: 87%
See 2 more Smart Citations
“…The correction was seldom more than 5 % RH when the RS92 temperature exceeded −60 • C. The correction was large for RS92 radiosonde values in the range 15-50 % RH and temperatures of −80 • C, with a maximum of +8.93 % RH. This pattern is similar to that of the correction table for the RS80 radiosonde in the daytime reported by Ciesielski et al (2010) (their Fig. 7b), but the values in Table 5 are much smaller.…”
Section: Humidity Correctionsupporting
confidence: 87%
“…This pattern is consistent with the results of Jauhiainen et al (2014), who indicated that the difference was largely due to the dissimilar approaches used to compensate for the heating effect of solar radiation on the humidity sensor. Similar dry biases were reported for the RS92 radiosonde with the earlier version of DigiCORA (Vömel et al, 2007;Yoneyama et al, 2008), although the dry bias was generally absent from later observations (Ciesielski et al, 2014;Yu et al, 2015) because the bias due to solar heating was removed by a correction scheme included in the v3.64 software or developed by Wang et al (2013). Figure 9 shows the relative difference of relative humidity in the daytime between the RS92 and RS41 radiosondes.…”
Section: Day-night Differencessupporting
confidence: 63%
See 1 more Smart Citation
“…However, these perturbation factors usually do not occur in the normal atmosphere. Furthermore, although the accuracy of radiosonde data is good overall, there are still unexpected errors in RS profiles and sometimes the errors are rather big (Wang et al, 2002;Ciesielski et al, 2010). In that case, it is not appropriate to compare the tomographic solution with radio sounding.…”
Section: Quality Of Entire Humidity Profilementioning
confidence: 99%
“…Several methods have been studied for decades, such as radio sounding, water vapor radiometer, sun photometers, GPS and others (Ciesielski et al, 2010;Perez-Ramirez et al, 2014;Li et al, 2016;Campmany et al, 2010;Liu et al, 2013). Compared with traditional water vapor observations, ground-based GPS water vapor measurement has advantages in high accuracy, high spatial-temporal resolution, all-weather availability and low-cost (Pacione and Vespe, 2008;Haase et al, 2003;Lee et al, 2010;Means, 2013;Lu et al, 2015).…”
mentioning
confidence: 99%